2008
DOI: 10.1136/hrt.2007.138263
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe for the treatment of primary (heterozygous-familial and non-familial) hypercholesterolaemia: NICE technology appraisal guidance

Abstract: This NICE technology appraisal guidance on ezetimibe for primary (heterozygous-familial and non-familial) hypercholesterolaemia should be read in conjunction with the NICE technology appraisal guidance on the initiation of statin therapy (Technology Appraisal 94) and in the context of the relevant NICE clinical guidelines.The full guidance 1 was published in the NICE technology appraisal guidance in November 2007. The guidance was developed using NICE's multiple technology appraisal process. Further informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The UK National Institute for Health and Clinical Excellence (NICE) guidance recently reviewed the results of several randomized controlled clinical trials with ezetimibe in patients with primary HC, with and without prior CVD 7. Average baseline LDL-C concentrations ranged from 3.4 to 6.5 mmol/L.…”
Section: Ezetimibe In Primary Hcmentioning
confidence: 99%
See 1 more Smart Citation
“…The UK National Institute for Health and Clinical Excellence (NICE) guidance recently reviewed the results of several randomized controlled clinical trials with ezetimibe in patients with primary HC, with and without prior CVD 7. Average baseline LDL-C concentrations ranged from 3.4 to 6.5 mmol/L.…”
Section: Ezetimibe In Primary Hcmentioning
confidence: 99%
“…To represent the population of people with HC that is not appropriately controlled with statin therapy, six 12-week, fixed-dose randomized controlled trials (RCTs, n = 3,610) were identified that compared ezetimibe plus statin therapy with statin therapy alone 7. The NICE Assessment Group carried out a meta-analysis on the RCTs.…”
Section: Ezetimibe In Primary Hcmentioning
confidence: 99%
“…They are most effective in reducing LDL-C 5 . Ezetimibe monotherapy is recommended as an option for treatment for adults who are intolerant to statin therapy, co-administered with initial statin therapy, is recommended as an option for treatment of adults who have been initiated on statin therapy when serum TC or LDL-C concentration is not appropriately controlled either after appropriate dose titration of initial statin therapy or because dose titration is limited by intolerance to the initial statin therapy 6 . This study was carried out in the outpatient department of Rizgary Teaching Hospital in Erbil city, for a period of 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…The recently issued guidance from the National Institute for Health and Clinical Excellence (NICE)1 on the cholesterol absorption inhibitor ezetimibe is welcome and summarised in this issue of Heart 2. NICE recommends its use in combination with a statin when more intensive low-density lipoprotein (LDL) lowering is indicated, and as monotherapy in the small proportion of patients who are intolerant of statin or in whom a statin is contraindicated.…”
mentioning
confidence: 99%